2023
DOI: 10.3847/psj/ad08ae
|View full text |Cite
|
Sign up to set email alerts
|

Near-IR Spectral Observations of the Didymos System: Daily Evolution Before and After the DART Impact Indicates that Dimorphos Originated from Didymos

David Polishook,
Francesca E. DeMeo,
Brian J. Burt
et al.

Abstract: Ejecta from Dimorphos following the DART mission impact significantly increased the brightness of the Didymos–Dimorphos system, allowing us to examine subsurface material. We report daily near-IR spectroscopic observations of the Didymos system using NASA’s IRTF that follow the evolution of the spectral signature of the ejecta cloud over 1 week, from 1 day before the impact. Overall, the spectral features remained fixed (S-type classification) while the ejecta dissipated, confirming that both Didymos and Dimor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…However, it has also been suggested that the gravitational interactions between slower ejecta and the Didymos binary system naturally can produce a secondary tail without the need for additional impact or disruption events (Ferrari et al 2024) or that the appearance of a secondary tail may be due to the projection of the ejecta cone and the viewing geometry of the observations . Spectral and color observations (Lin et al 2023;Polishook et al 2023;Ieva et al 2024) as well as polarimetry observations (Bagnulo et al 2023;Gray et al 2024) provide evidence that the ejecta excavated from Dimorphos share similar properties to Didymos as an S-type asteroid. Extended polarimetry observations show that an immediate drop in polarization was associated with DARTʼs impact event and that lower polarization persisted through all the subsequent months of observations; this suggests that smaller or brighter particles than the pre-impact surface were ejected by DART and that these particles continue to exist in the system, either in orbit or deposited on the surface (Gray et al 2024;Penttilä et al 2024).…”
Section: Ejecta Observations and Evolutionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, it has also been suggested that the gravitational interactions between slower ejecta and the Didymos binary system naturally can produce a secondary tail without the need for additional impact or disruption events (Ferrari et al 2024) or that the appearance of a secondary tail may be due to the projection of the ejecta cone and the viewing geometry of the observations . Spectral and color observations (Lin et al 2023;Polishook et al 2023;Ieva et al 2024) as well as polarimetry observations (Bagnulo et al 2023;Gray et al 2024) provide evidence that the ejecta excavated from Dimorphos share similar properties to Didymos as an S-type asteroid. Extended polarimetry observations show that an immediate drop in polarization was associated with DARTʼs impact event and that lower polarization persisted through all the subsequent months of observations; this suggests that smaller or brighter particles than the pre-impact surface were ejected by DART and that these particles continue to exist in the system, either in orbit or deposited on the surface (Gray et al 2024;Penttilä et al 2024).…”
Section: Ejecta Observations and Evolutionmentioning
confidence: 87%
“…The total mass of the binary system is constrained by the pre-impact orbit period; though, given that Didymos is significantly larger than Dimorphos, this does not provide a direct constraint on the mass of Dimorphos. Telescopic observations of the Didymos system taken after DARTʼs impact, during the following days when the signal from the Didymos system was dominated by ejecta from Dimorphos, indicate that Dimorphos, like Didymos, is an S-type asteroid (Bagnulo et al 2023;Lin et al 2023;Polishook et al 2023;Gray et al 2024;Ieva et al 2024;Lazzarin et al 2024). While these telescopic observations provide evidence that the composition of Dimorphos is the same as Didymos, the density of the objects could still be different depending on the macroporosity of the bodies.…”
Section: Dart-4a: Determine the Momentum Enhancement Factormentioning
confidence: 99%
“…Such a global layer would require ∼5 × 10 6 kg of material to be redeposited, which is ∼10%-40% of the estimated mass that was observed to be ejected by the DART impact (i.e., 1.3-6.4 × 10 7 kg; Roth et al 2023). Furthermore, no permanent spectral changes were observed on Didymos (Polishook et al 2023), which suggests that no system-wide resurfacing occurred at even thinner layers.…”
Section: Thermal Inertia Interpretation and Implications For The Dart...mentioning
confidence: 99%
“…An example of such a case could be the Didymos system, the target of NASAʼs Double Asteroid Redirection Test (DART) mission. Polishook et al (2023) obtained NIR spectra of Didymos before and after the impact. They found that the ejecta cloud released from Dimorphos was the main contributor to the light of the system for ∼40 hr after the impact.…”
Section: Space Weathering and Resurfacing Processesmentioning
confidence: 99%